2022
DOI: 10.1063/5.0090356
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory leakage flow fraction for surgical masks with varying gaps and filter materials

Abstract: Leakage flows due to a poor fit can greatly reduce the mask protection efficiency. However, accurate quantification of leakages is lacking due to the absence of standardized tests and difficulties in quantifying mask gaps. The objective of this study is to quantify the leakage flows around surgical masks with gaps of varying areas and locations. An integrated ambient-mask-face-airway model was developed, with a pleated surgical mask covering an adult's face, nose, and chin. To study the gap effects, the mask e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In fact, even a small error on the 3D reconstruction of the face-mask assembly can return a significant misprediction of the leaked flow. This is also confirmed by the very limited validations of the CFD results, considering, at best, a benchmark in terms of velocity at a point and associated with large error bars [61]. Despite these limitations, numerical investigations by Solano and co-workers [38], [62] and Xi et al [61] confirmed that a high-porosity mask (i.e.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, even a small error on the 3D reconstruction of the face-mask assembly can return a significant misprediction of the leaked flow. This is also confirmed by the very limited validations of the CFD results, considering, at best, a benchmark in terms of velocity at a point and associated with large error bars [61]. Despite these limitations, numerical investigations by Solano and co-workers [38], [62] and Xi et al [61] confirmed that a high-porosity mask (i.e.…”
Section: Discussionmentioning
confidence: 90%
“…Computational fluid dynamics simulations [38], [61] have been conducted to study the airflow pattern around a worn mask during breathing and coughing, evidencing how misfitting a mask create leakage through gaps compromising its efficacy [61], and that leakage correlates with lower filter porosity because of the increased differential pressure of the filtering materials [38]. All these results corroborate the recommendation for a tight fitting and a breathable material, and the necessity of identifying comprehensive performance metrics which include the effect of leakage, such as the TFE defined in our study.…”
Section: Discussionmentioning
confidence: 99%
“…and of mask designs at a reasonable cost. CFD has been used to quantify the partition of the inhaled airflow between the flow going through the filter media and the flow through the leaking spots, 87 with a focus on the impact of the gap area considering various positions of leaking spots along the faceseal interface. The model showed that a gap of 1 cm 2 was sufficient to drive 17% of the flow through the leaks, thus being unfiltered (a gap of 4.3 cm 2 led to 60% of the inhaled flow going through the leaks).…”
Section: Modeling Inward and Outward Leaking Flowsmentioning
confidence: 99%
“…A complete N2B delivery involves four stages: (1) intranasal drug delivery to the olfactory mucosa, (2) drug transport from the olfactory mucosa to the brain (tissue transport), (3) drug action in the brain (pharmacodynamics), and (4) drug elimination from the brain and body ( Figure 1 b). One of the first researches on the use of the olfactory path for neurological disorder treatment was conducted by researchers [ 14 , 15 ], who explored the intranasal route to send nerve growth factors to the brain (i.e., the second stage in Figure 1 b). Since then, efforts to enhance the transportation of small interfering molecules to the brain have been actively pursued [ 16 ].…”
Section: Introductionmentioning
confidence: 99%